CONCEPTS IN PSYCHOLOGY AND THE NEED TO CRITICALLY REFLECT ON THEM - Thea IONESCU (Studia Universitatis Babes-Bolyai, 2022)
This opinion article raises the issue of conceptual crisis in psychology, i.e. the problem of having several meanings underlying many of the concepts we study. After exemplifying with the concepts of "flexibility" and "cognition", I propose three avenues on the way to conceptual clarity, and stress the need for a stronger theoretical psychology.